STUDI EFEKTIVITAS SISTEM OLAH TANAH DAN TEKNIK PENGENDALIAN GULMA TERHADAP PERTUMBUHAN DAN HASIL PADI GOGO (Oryza sativa L.) DI LAHAN KERING INDRAMAYU JAWA BARAT - Abadi, Slamet (Jurnal Pertanian Presisi (Journal of Precision Agriculture), 2019)
The study aims to get the best weed-control system and soil-processing techniques so as to increase the growth andÂ  yield of upland rice (Oryza sativa L.) in the drylands of Indramayu, West Java. The results of this study show the effect of interactions between soil process systems and weed control techniques on the number of children aged 60 days after planting, the height of plants at the time of the harvest, the weight of 1000 grains of rice and the number of mallei per clumps. The system of self-sustaining soil process against all observation variables has no real effect. Self-contained weed control techniques against the number of 30 DAP aged tillers and in the time leading up to harvest there was a real influence. For the height of the 30 DAP and 60 DAP life plants, there are real influences as well as grain per mallei, and the milled dry grain is a real influence. On the self-sufficient influence of the highest milled dry grain yielding, soil process system is minimum soil process system with an average of 3.69 kg/plot and there is no significant difference to the treatment of the perfect soil process system with an average of 3.45 kg/plot. On the self-contained influence weed control technique, the highest giving dry grain yield is manually weeded once, age 21 DAP+ pre herbicides grow with an average of 4.07 kg/plot differently real to all treatment of the others